Harvesting hope : the story of Cesar Chavez - Krull, Kathleen; Morales, Yuyi (San Diego : Harcourt, 2003)
A biography of Cesar Chavez, from age ten when he and his family lived happily on their Arizona ranch, to age thirty-eight when he led a peaceful protest against California migrant workers' miserable working conditions.
Notable/Best Books (A.L.A.).
School Library Journal starred.
Wilson's Children.
Book Links (A.L.A.), January 2009.
Horn Book, October 2003.
Kirkus Review, July 2003.
Keywords: Chavez, Cesar, -- 1927-1993 -- Juvenile literature; Chavez, Cesar, -- 1927-1993.; Chavez, Cesar, -- 1927-1993.; United Farm Workers -- History -- Juvenile literature; United Farm Workers; United Farm Workers; Labor leaders -- United States -- Biography -- Juvenile literature; Mexican Americans -- Biography -- Juvenile literature; Labor leaders; Mexican Americans -- Biography; Migrant labor; Labor leaders -- Biography; Mexican Americans -- Biography; Migrant labor